Effect of phase change materials on the thermal behavior of biomass-based composites - Benjamin Durakovic; Nadir Mujković; Alma Hudović-Kljuno; Emira Gibanica (Heritage and Sustainable Development)
This research explores the thermal performance of biomass-based composite panels enhanced with Phase Change Materials (PCM) for energy-efficient building applications. The experimental method under lab-controlled conditions was used to investigate thermal performances. Four samples of PCM-biomass-based composite were fabricated using encapsulated PCM, straw, and mortar as a binding material, and four sample without PCM as a reference. The effective thermal conductivity of each sample was determined using the guarded hot plate method under steady-state conditions. Results indicate that the incorporation of PCM does not significantly alter the thermal conductivity of the composite, but it enhances the material’s ability to store thermal energy. Compared to conventional construction materials, both the reference and PCM-enhanced samples exhibit superior thermal insulation properties, making them promising candidates for sustainable building applications. The findings suggest that optimizing PCM concentration and distribution could further enhance thermal performance, contributing to the development of passive energy-saving solutions.